A Therapeutic Approach Against Leishmania donovani by Predicting RNAi Molecules Against the Surface Protein, gp63 - Chowdhury, Farhana T.; Shohan, Mohammad U.S.; Islam, Tasmia; Mimu, Taisha T.; Palit, Parag (Current Bioinformatics, 2019)
Background: Leishmaniasis is a disease caused by the Leishmania sp. and can be classified into two major types: cutaneous and visceral leismaniasis. Visceral leishmaniasis is the deadlier type and is mediated by Leishmania donovani and involves the establishment of persistent infection and causes damage to the liver, spleen and bone marrow. With no vaccine yet available against leishmaniasis and the current therapeutic drugs of leishmaniasis being toxic and expensive; an alternative treatment is necessary. Objective: Surface glycocalyx protein gp63, plays a major role in the virulence and resulting pathogenicity associated with the disease. Henceforth, silencing the gp63 mRNA through the RNA interference system was the aim of this study. Methods: In this study two competent siRNAs and three miRNAs have been designed against gp63 for five different strains of L. donovani by using various computational methods. Target specific siRNAs were designed using siDirect 2.0 and to design possible miRNA, another tool named IDT (IntegratedDNA Technology). Screening for off-target similarity was done by BLAST and the GC contents and the secondary structures of the designed RNAs were determined. RNA-RNA interaction was calculated by RNAcofold and IntraRNA, followed by the determination of heat capacity and the concentration of duplex by DNAmelt web server. Results: The selected RNAi molecules; two siRNA and three miRNA had no off-target in human genome and the ones with lower GC content were selected for efficient RNAi function. The selected ones showed proper thermodynamic characteristics to suppress the expression of the pathogenic gene of gp63.
Keywords: Leishmaniasis